Lasersko osvetljevanje - Šubic, Matjaž (Matrika, 2021)
Laser illumination is used in many different fields such as industry and medicine. In recent years there are more and more studies on how to use laser light as a light source in screens and projection systems. Compared to the currently used light sources, lasers offer much better color gamut, higher light output, and a much longer lifespan. Laser lighting can also be used to capture fast-moving objects. With fast and powerful laser pulses, we can freeze the image and take a sharp image of the object. Due to laser illumination, the image quality will depend on the length and intensity of the laser pulse. With laser illumination, we can shoot hot objects that emit energy in the form of light. Because the laser light has a narrow spectrum, with use of a band-pass filter only the light in the spectral range of the laser will reach the camera sensor. As a result, we get an image of an object without thermal light. The biggest problem with laser illumination are speckles, which appear as an unwanted grainy pattern on the illuminated surface and reduce the image quality. Various methods can reduce the contrast of speckles below 1 %.
Keywords: fizika; laser illumination; lasersko osvetljevanje; physics